Bilateral control system of the space robot with large delays - G. Alferov; P. Efimova; D. Shymanchuk; S. Kadry; M. N. Meqdad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The main obstacle of the construction of efficient remote-control systems for space robots is a significant delay in transmissions of control signals to robots from the earth-based control center and receiving feedback signals. This significantly complicates the solution of control problem, especially if robot’s manipulators move objects that have mechanical constraints. Our work describes a method for bilateral control of a space robot with large delays. The uniqueness of this method lies in the special structure of the control algorithm. Bilateral control implies force feedback necessary for the interaction of a space robot with objects that have holonomic connections. We present a new mathematical model of the elements of the bilateral control system and their computer implementation using specific examples.